Analisis Open Government dan e-Government di Indonesia Berdasarkan Kerangka Kerja SDGs: Studi Kasus Desa Melung, Kabupaten Banyumas - Yamin, Muhammad; Darmawan, Arief Bakhtiar; Zayzda, Nurul Azizah; Ash-Shafikh, Mayza (Jurnal Hubungan Internasional, 2018)
This research paper aims to analyze the readiness of local government in Indonesia in order to fulfill the Sustainable Development Goals (SDGs) initiated by the United Nations for rural area level. The author analyzes the open government readiness in Melung Village, Banyumas Districts, Central Java, as a specific case to see the strategy and application of e-government model that was conducted by the government. This paper argues despite the location in the rural area, the government of Melung Village has utilized the system based on the SDGs framework, such as an action to replace paper-based administration into electronic government. This effort was taken to improve the efficiency of public services based on quality and accountability which leads to more active government participation in sharing information with its citizen. Nevertheless, the local government of Melung Village efforts were not good enough since they still need assistance from government and state-owned company. Therefore, the result of the research might strengthen local government institutional and able to fulfill the development goals as is set in SDGs framework.